Is unipolar mania a distinct entity: findings from the bipolar disorder course and outcome study from India (BiD-CoIN study). (2nd November 2021) - Grover, Sandeep; Avasthi, Ajit; Chakravarty, Rahul; Dan, Amitava; Chakraborty, Kaustav; Neogi, Rajarshi; Desouza, Avinash; Nayak, Omkar; Praharaj, Samir Kumar; Menon, Vikas; Deep, Raman; Bathla, Manish; et al.
Abstract: Aim: This study aimed to evaluate the prevalence of unipolar mania (UM) in a group of patients of bipolar disorder (BD). Additionally, effort was made to evaluate the demographic, clinical and treatment related factors, which distinguish subjects of UM from BD. Methodology: Seven hundred and seventy-three patients with BD, of at least 10 years duration, recruited from 14 General Hospital Units of tertiary care centers from India were evaluated for UM. Results: The prevalence of UM, varied from 5.4% to 20.3%, depending on the definition used. With the most stringent definition of ≥4 episodes of mania and at least 5 years of follow-up, the prevalence of UM was 5.4%. Compared to patients of BD, who have episodes other than mania too, those with UM had lower proportion of patients with lifetime history of suicide attempts, spent less time in the episodes in their lifetime and had lower severity of residual depressive and manic symptoms. Further, compared to those with episodes other than mania too, those with UM had higher number of manic episodes per year of illness, had higher proportion of patients who had more than five episodes in the lifetime and had higher proportion of those with at least one episode with psychotic symptoms in the lifetime. Conclusion: The present study suggests that a small proportion of patients with BD have UM course and this runs a different clinical course compared to that seen in patients with traditionally recognized as BD.